2017
DOI: 10.1007/s13593-017-0479-x
|View full text |Cite
|
Sign up to set email alerts
|

Crop-livestock integration determines the agroecological performance of mixed farming systems in Latino-Caribbean farms

Abstract: Characterizing and understanding the complexity of numerous interactions occurring in mixed farming systems is still a methodological challenge. We hypothesize that farm functioning features in terms of crop-livestock integration practices impact the agroecological performance of the system, which will be also affected by the farm context. In order to analyze crop-livestock integration in a holistic way, a set of seventeen mixed farming systems from three contrasting socioeconomic regions of the humid tropics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 29 publications
1
26
0
2
Order By: Relevance
“…The study's conceptual framework is derived from the two-compartment network model developed by Stark et al [49] in order to examine the input and output flows within an integrated crop-livestock system in Latino-Caribbean farms. However, in this study, the framework has been modified to show the two-way interaction between the two farming systems (i.e., crop farming or system 1 and livestock farming or system 2).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The study's conceptual framework is derived from the two-compartment network model developed by Stark et al [49] in order to examine the input and output flows within an integrated crop-livestock system in Latino-Caribbean farms. However, in this study, the framework has been modified to show the two-way interaction between the two farming systems (i.e., crop farming or system 1 and livestock farming or system 2).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…(1 Fig. 1 The conceptual framework adapted from Stark et al [49] where D i denotes diversification, N i is the total number of household-managed units of diversity options in the sample, and S i is the number of household-managed units of diversity for the ith household. Hence, for this study, the definitions of N i and S i regarding the various systems are shown in Table 1.…”
Section: The Margalef Indexmentioning
confidence: 99%
“…The existence of livestock makes it necessary to have grasslands that, where permanent, increase biodiversity at field level. Crop/livestock integration is especially effective in promoting resilience of farming systems and contributes partially to system productivity in Latin America [101]. Mediterranean farms are characterized by forage availability across the year mainly linked to woody vegetation or costly irrigated systems to overcome water shortage.…”
Section: Discussionmentioning
confidence: 99%
“…A second example includes pastures that are integrated into silvo-pastoral systems to increase the production of meat and timber, while at the same time increasing CS and HB. Tree-livestockcrop integrated systems may foster positive interactions between different ecosystem services and resource-use efficiency in the Amazon and the Cerrado (Campos et al, 2015;da Conceição et al, 2017;Stark et al, 2017;Gil et al, 2018). Considering the supply matrix (Figure 2.3), this pathway means that within a landscape unit (e.g., mechanized agriculture on clayey plateaus) the supply of all ecosystem services can be increased (i.e., the size of the bubbles) by adopting management practices that modify soil properties as well as energy, nutrient and water fluxes at the field and farm level.…”
Section: Pathways To Match Supply and Demand Of Ecosystem Servicesmentioning
confidence: 99%